A literature review for large-scale health information system project planning, implementation and evaluation. (January 2017) - Sligo, Judith; Gauld, Robin; Roberts, Vaughan; Villa, Luis
Highlights: The literature about implementation and evaluation of Health information Systems (HIS) is reviewed and summarised. Successful implementation of HIS requires organisational change. Organisational, technological and human factors impact on the effectiveness of HIS implementation. HIS evaluations have been of mixed quality. They should be well-funded, planned, rigorous and ongoing. Abstract: Information technology is perceived as a potential panacea for healthcare organisations to manage pressure to improve services in the face of increased demand. However, the implementation and evaluation of health information systems (HIS) is plagued with problems and implementation shortcomings and failures are rife. HIS implementation is complex and relies on organisational, structural, technological, and human factors to be successful. It also requires reflective, nuanced, multidimensional evaluation to provide ongoing feedback to ensure success. This article provides a comprehensive review of the literature about evaluating and implementing HIS, detailing the challenges and recommendations for both evaluators and healthcare organisations. The factors that inhibit or promote successful HIS implementation are identified and effective evaluation strategies are described with the goal of informing teams evaluating complex HIS.